2019
DOI: 10.1111/syen.12409
|View full text |Cite
|
Sign up to set email alerts
|

Combined molecular and morphological data provide insights into the evolution and classification of Chilocorini ladybirds (Coleoptera: Coccinellidae)

Abstract: Ladybirds of the cosmopolitan tribe Chilocorini prey mainly on coccids and include several important biocontrol agents. The phylogenetic relationships of Chilocorini are poorly known. In this paper, we provide a phylogenetic reconstruction of Chilocorini containing all 27 genera based on five molecular markers and 86 adult morphological characters. Morphological character states were mapped on the combined data tree from Bayesian inference to analyse morphological traits of each genus. Sixteen morphological ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In agreement with previous studies (Magro et al ., 2010; Che et al ., 2017; Escalona et al ., 2017; but see also Li et al ., 2020), we recovered Coccinellini sister to Chilocorini. Interestingly this relationship is not supported by morphological evidence (Ślipiński & Tomaszewska, 2010).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In agreement with previous studies (Magro et al ., 2010; Che et al ., 2017; Escalona et al ., 2017; but see also Li et al ., 2020), we recovered Coccinellini sister to Chilocorini. Interestingly this relationship is not supported by morphological evidence (Ślipiński & Tomaszewska, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…The recent study of Li et al . (2020), focussing on the coccidophagous Chilocorini, recovered a median age of 168 Ma for Coccinellidae, and recovered a median age of 70 Ma for Coccinellini; however, only three species representing two genera of Coccinellini were included in their work. Considered altogether these studies suggest a median age between 105 and 196 Ma for the family, with uncertainty resulting from non‐overlapping confidence intervals (e.g., see McKenna et al ., 2015; Toussaint et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The recent phylogenetic studies of Chilocorini indicated that the relationship between Exochomus and Brumus is not so close. Exochomus is the sister group of a large clade containing various genera, for example, Xanthocorus , Priscibrumus , Parexochomus , Brumus and Brumoides , while Brumus is closely related to Brumoides ( Li et al 2020 ). Actually, Brumus can be easily distinguished from Exochomus by the following characters: elytral epipleuron more or less horizontal; tarsal claws without basal tooth, only slightly swollen at base.…”
Section: Discussionmentioning
confidence: 99%
“…Many species of this tribe are widely used as biological control agents. In recent years, phylogenetic and evolutionary studies of Chilocorini indicated that this tribe is a monophyletic group, closely related to the tribe Coccinellini ( Magro et al 2010 , Seago et al 2011 , Escalona et al 2017 , Che et al 2017 ) or Plotinini ( Li et al 2020 ). At present, Chilocorini contains 22 genera and more than 280 species distributed worldwide ( Łączyński and Tomaszewska 2012 , Li et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation